Spectroscopic, electrochemical and X-ray diffraction studies on nickel(II)-complexes of acetophenone thiosemicarbazones substituted six-carbon groups - KOCA, ATIF (ELSEVIER SCIENCE SA, 2016)
Reactions of [Ni(PPh3)(2)Cl-2] with 3-Bromo-5-chloro-2-hydroxyacetophenone-N-4-hexyl ((LH2)-H-1), cyclohexyl (L2H2) and phenyl ((LH2)-H-3)-thiosemicarbazones resulted in four coordinated (ONSP) nickel(II) complexes, [Ni(L-1)(PPh3)] (1), [Ni((LH)-H-2)(PPh3)]center dot Cl (2) and [Ni(L-3)(PPh3)]center dot C2H5OH (3). The structures of 1-3 were determined by spectroscopic and single crystal X-ray diffraction methods. While formation of complexes 1 and 3 occurs through the doubly deprotonated forms of the thiosemicarbazone ligands (L-1 and L-3), complex 2 consists of mono deprotonated ligand ((LH)-H-2). Cyclic voltammetry and square wave voltammetry studies of the compounds showed that all ligands represented one irreversible reduction and two irreversible oxidation processes. Complexes 1-3 illustrated a metal based reduction and a metal based oxidation processes in addition to the ligand based electron transfer reactions. In situ spectroelectrochemical measurements were employed to determine the spectra of electrogenerated species of the complexes and to assign the redox processes. The influences of the N-4-substituent types on structural and electrochemical features of the compounds were discussed. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Thiosemicarbazone; Nickel(II) complex; Triphenylphosphine; Crystal analysis; Electrochemistry; Spectroelectrochemistry; IN-SITU SPECTROELECTROCHEMISTRY; CRYSTAL-STRUCTURE; COPPER(II) COMPLEXES; MOLYBDENUM COMPLEX; DNA-BINDING; DERIVATIVES; DINUCLEAR; NI(II); LIGAND; TRIPHENYLPHOSPHINE